Expression of cyclooxygenase-2 in the mammary gland tissue of goats affected with caprine contagious agalactia. Issue 1 (April 2015) - Rodríguez, Francisco; Poveda, José B.; Jaber, José R.; Orós, Jorge; Rodríguez, José L.
Highlights: COX-2 can be demonstrated by immunohistochemistry in caprine mammary tissue. COX-2 expression was associated with areas of M. agalactiae infection. Macrophages and neutrophils were COX-2 positive. Epithelial cells, endothelial cells and fibroblasts were COX-2 positive. Abstract: Caprine contagious agalactia is a syndrome most frequently caused by Mycoplasma agalactiae. The pathogenic mechanisms that allow M. agalactiae to persist in the mammary gland tissues following infection, despite a prominent inflammatory response, are yet to be fully established. The aim of the present study was to investigate cyclooxygenase (COX)-2 in the mammary gland of goats during M. agalactiae infection. COX-2 expression was evaluated by immunohistochemistry in the inflammatory lesions of 10 goats affected with M. agalactiae -induced mastitis (five naturally infected and five experimentally infected). Epithelial cells, macrophages, endothelial cells, fibroblasts and, to a lesser extent, neutrophils demonstrated positive immunostaining for COX-2, associated with areas of mastitis and with the presence of M. agalactiae antigen. These research findings suggest that COX-2 is involved in the inflammatory response that occurs in caprine contagious agalactia.